Pemanfaatan Kulit Buah Kakao sebagai Media Adsorpsi Logam Besi (Fe) dan Mangan (Mn) pada Air Sumur - Nurfahma, Nurfahma; Rosdiana, Rosdiana; Adami, Aryani (Universitas Muhammadiyah Kendari, 2021)
This study aims to determine the percentage reduction in iron (Fe2+) and manganese (Mn2+) content in well water using carbon from cocoa peel as an adsorption media with media height variation. The results of this study indicate that well water sample contains iron (Fe2+) levels of 1.39 mg/L and manganese (Mn2+) of 0.76 mg/L. After filtration with 60 minutes contact using carbon of cocoa peel as an adsorption media without activation, iron content and manganese content in well water decreased. The percentage reduction of iron (Fe2+) content in media height 70 cm, 80 cm and 90 cm were 76.98%, 84.17% and 98.21%. Meanwhile, the percentage in manganese (Mn2+) content at 70 cm media height was 98,93% and archived an optimum reduction at 80 cm and 90 cm media height which is 99.79% with 60 minute contact time.